Contexts of simulation in healthcare - Studnicka, Katarzyna; Zalewski, Jakub (Nursing in the 21st Century, 2021)
CONTEXTS OF SIMULATION IN HEALTHCARE Introduction. Simulation in the education of future nursing staff dates back to 1911. Technological progress over the years has resulted in the situation in which nowadays Medical Simulation Centres use top-class equipment, training is supported by standards, and students master their skills, not only the practical ones, but also those related to team communication or working under time pressure. In addition, virtual simulation is becoming more and more popular, which, in the current times of the coronavirus pandemic, allows for conducting classes. Aim. To present the evolution and the importance of medical simulation in the training of nurses. Method. Non-systematic review of the topic literature; the selection of documents (in Polish and English) for the years 2009-2021 consistent with the aim of the review. Summary. Medical simulation centres are places which not only serve the purpose of developing future medical staff, but also constitute an ideal space for professional development of the already professionally active medical staff.